Development of the indigenous people of “amuzgo de xochistlahuaca.” Between tradition and modernization - Ota Otani, Gen (2020)
Each indigenous people in each Latin American country has its own sociocultural and historical characteristics that have developed in a specific local space, therefore each town is different. However they all share something in common, the fact that they are named “Indians” and they are identified as the opposite of something called “modern”. On the other hand, in recent decades we have seen a dynamism and a transformation among these inhabitants that suggest a rethinking of these ideas.  In this article, I will describe and address the relationship that exists between indigenous groups and the idea of ​​“modernity” and also how they have developed in their recent historical trajectory on this issue considering the socio-historical development that the Amuzgo people have lived in Xochistlahuaca located in the region of the Costa Chica in the State of Guerrero in Mexico.